Patterns and Factors Associated with Dyslipidemia Among Patients with Diabetes Mellitus Attending Hoima Regional Referral Hospital, Uganda - Hirsi AM; Abdi AA; Peris A; Jacinto A; Muhammad P; Nur IA; Mohamud MH; Hussein M; Qaws A; Jayte M (International Journal of General Medicine)
Abishir Mohamud Hirsi, Awil Abdukadir Abdi, Alina Peris, Amandua Jacinto, Propser Muhammad, Ibrahim Ahmed Nur, Muktar Hassan Mohamud, Mustafa Hussein, Abdi Qaws, Mohamed Jayte Department of Internal Medicine, Faculty of Clinical Medicine and Dentistry, Kampala International University, Ishaka, Bushenyi, UgandaCorrespondence: Abishir Mohamud Hirsi, Email abshir.heirsi@gmail.comBackground: Dyslipidemia in Sub-Saharan Africa has been on the disproportionate rise among diabetes patients across various contextual settings due to its patterns and associated factors. This study determined the patterns and factors associated with dyslipidemia among diabetes patients attending Hoima Regional Referral Hospital (HRRH).Methods: This was a hospital-based cross-sectional study conducted at HRRH between October 2022 and January 2023, enrolled 375 adult diabetes patients consecutively from diabetic outpatient clinic. Data on socio-demographic, behavioral, medical history, physical examination, and laboratory diagnoses were collected and summarized using descriptive statistics. Patterns of dyslipidemia were presented as a proportion of each lipid profile either singly or in combination expressed as a percentage. In the bivariate analysis, variables with p-values < 0.2, crude odds ratios of ≥ 2 or ≤ 0.5, or those with biological plausibility were included in a multiple logistic regression model. Factors with p-values < 0.05 were considered statistically significant. All analyses were conducted using Stata version 17.Findings: Of the 375 diabetes patients, 260 (69.3%) had abnormal total cholesterol (TC), and 185 (49.3%) had two lipid profile abnormalities. The majority of the patients were female, 235 (62.7%), and 38 (10.1%) had a diagnosis of coronary heart disease (CHD). Additionally, 134 (35.7%) were overweight, and 39 (10.4%) were obese. Female patients had higher odds of dyslipidemia (Adjusted Odds Ratio [AOR] = 2.2, 95% CI: 1.02– 4.86, p = 0.045). Those with coronary heart disease (CHD) had increased odds of dyslipidemia (AOR = 4.1, 95% CI: 1.51– 11.07, p = 0.006). All diabetes patients who were overweight or obese had dyslipidemia (p < 0.001).Conclusion: The most common pattern of dyslipidemia in patients with diabetes was elevated total cholesterol, followed by high low-density lipoprotein, associated with overweight, obesity, female gender, and CHD. Routine screening of lipid profiles, BMI, and CHD in diabetic clinics is crucial for early intervention and improved outcomes.Keywords: diabetes mellitus, dyslipidemia, total cholesterol, low-density lipoprotein, coronary heart disease, risk factors, Uganda